(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
Education is vital for dynamic growth and development. The higher education is important for every country. It is regulated by systemic regulations and bylaws. In this paper, the interest is directed at the salaries of employees in the state higher education, given their long-standing lag. The forms of payment of employees are analyzed and the salary level is compared with the averages in the country. The paper proposes solutions that are of importance for this issue, especially for forming a payroll model that will correspond to the meaning of the educational segment of the society. The status of the professors as service providers is inadequate and is not regulated from the aspect of the salaries and the benefits for the invested labour. Without motivated teachers and professors who implement the higher education system, changes and results cannot be expected in terms of the quality of human resources produced at universities. In the absence of a culture of appreciation of the knowledge, postulates are formed which in the long run cannot change the values of the systems in society.